Pengaruh Kualitas Pelayanan Terhadap Kepuasan Konsumen Pada Hotel DF Pekanbaru - Yenni, Astuti; Imrialis, Imrialis (Eko dan Bisnis: Riau Economic and Business Review, 2025)
This research entitled The Influence of Service Quality on consumer satisfaction at the DF Hotel Pekanbaru aims to analyze the Influence of Service Quality on consumer satisfaction at the DF Hotel Pekanbaru. The population and sample in this study used a saturated sample technique, namely 100 respondents. Using descriptive and quantitative research methods then analyzed using a simple linear regression method. The average value of 4.05 means that it is included in the Fairly Agree (moderate) class interval in influencing Consumer Satisfaction. Based on the results of the t test, the calculated t value is 5.011 which is greater than the t table of 1.660 with a significance level of 0.015 which is smaller than α 5% (0.05). This means that supervision has a positive and significant effect on consumer satisfaction. The correlation/relationship value (R) is 0.452. From this output, a coefficient of determination (R Square) of 0.204 is obtained, which means that the influence of the independent variable Service Quality on the dependent variable is influenced by other variables not included in this research.